Effects of instruction in jumping technique and experience jumping on ground reaction forces - Prapavessis, H.; McNair, P. J. (Journal of Orthopaedic & Sports Physical Therapy, 1999)
Abstract: Study Design: Randomized, controlled trial. Objective: To determine the roles that augmented feedback from instruction in jumping technique and sensory feedback from experience jumping play in assisting individuals to land softly from a jump. Background: Jumping and landing activities play a major role in many sports and daily activities. Feedback may assist individuals in decreasing landing forces and thus reduce the chances of sustaining an injury. Methods and Measures: Nonimpaired subjects (n = 91) were randomly assigned to either an augmented or sensory feedback condition. All subjects were asked to jump from a box 300 mm in height and land as softly as possible on a force plate. Pre-intervention ground reaction forces (GRF) were recorded. Subjects in the augmented feedback condition were then given instructions to focus on hip and knee joint motion as well as a forefoot landing technique for their next jump. Subjects in the sensory feedback condition were asked to use the experience of their first jump to land softly for their next jump. Post-intervention GRFs were recorded and all GRFs were expressed as a multiple of body weight. Results: Those in the augmented condition significantly reduced their GRF scores from pre- (mean = 4.53 ± 1.51) to post- (mean = 3.57 ± 1.10) jump, whereas those in the sensory condition did not (mean pre GRF = 4.51 ± 1.77; mean post GRF = 4.33 ± 1.54). Conclusions: High ground reaction forces may be a precipitating factor associated with an injury, where the site of tissue damage would benefit from decreased forces. These findings support the use of instructions related to joint motion to reduce landing forces. full text:http://www.udel.edu/PT/clinic/may/prapavessis.pdf